Indigenous people's innovation : intellectual property pathways to development - Drahos, Peter, 1955-; Frankel, Susy (ANU E Press, 2012)
Traditional knowledge systems are also innovation systems. This book analyses the relationship between intellectual property and indigenous innovation. The contributors come from different disciplinary backgrounds including law, ethnobotany and science.
Keywords: Ethnoscience.; Traditional ecological knowledge.; Intellectual property.; Indigenous peoples -- Legal status, laws, etc.; Ethnic studies.; Indigenous peoples.; Intellectual property law.; Law.; Laws of Specific jurisdictions.; Social groups.; Society and culture: general.; Society and social sciences Society and social sciences.; SOCIAL SCIENCE -- General.; Immaterialgüterrecht; Indigenes Volk; Kulturerbe; Ethnosciences.; Savoirs écologiques traditionnels.; intellectual property.; traditional knowledge.; indigenous studies.; Electronic book; Electronic books.